2020
DOI: 10.1111/dgd.12663
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling early stages of endoderm development in epiblast stem cell aggregates with supply of extracellular matrices

Abstract: Endoderm precursors expressing FoxA2 and Sox17 develop from the epiblast through the gastrulation process. In this study, we developed an experimental system to model the endoderm-generating gastrulation process using epiblast stem cells (EpiSCs). To this end, we established an EpiSC line i22, in which enhanced green fluorescent protein is coexpressed with Foxa2. Culturing i22 EpiSCs as aggregates for a few days was sufficient to initiate Foxa2 expression, and further culturing of the aggregates in Matrigel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, evidence suggests that laminin, a major component of Matrigel, can direct human ES cells toward the endoderm lineage [42]. Furthermore, studies have demonstrated that culturing EPI stem cells in Matrigel results in up-regulated levels of endoderm-related transcription factors such as Sox17 [43], further supporting the notion that Matrigel influences lineage commitment towards endoderm.…”
Section: Discussionmentioning
confidence: 92%
“…However, evidence suggests that laminin, a major component of Matrigel, can direct human ES cells toward the endoderm lineage [42]. Furthermore, studies have demonstrated that culturing EPI stem cells in Matrigel results in up-regulated levels of endoderm-related transcription factors such as Sox17 [43], further supporting the notion that Matrigel influences lineage commitment towards endoderm.…”
Section: Discussionmentioning
confidence: 92%
“…or Nacalai) was used to dissociate cells except for the KN3 line, where the cell sheets were mechanically dissociated into cell clumps (Table 1). RNA was extracted from the cultures as described in Inamori et al (2020). To differentiate the NSCs into neurons or glial cells, the dissociated cells were plated on uncoated dishes and cultured in basic culture medium for 3 days for neuronal development, or in medium containing 1% fetal bovine serum for 5 days for glial cell development.…”
Section: Mouse Episc and Nsc Culturesmentioning
confidence: 99%
“…Principal component analysis of the data was performed using Subio software (Subio Inc., Amami, Japan). RT-qPCR analysis of individual mRNA levels was performed as described in Inamori et al (2020) using the primers described by Iwafuchi-Doi et al (2012), except for Hoxb6 (Forward, TTCCTATTTCGTGAACTCCACCTT; Reverse, CCG CATAGCCAGACGAGTAGA) and Hoxa7 (Forward, ACGCGC TTTTTAGCAAATATACG; Reverse, GGGTGCAAAGGAGCA AGAAG) (Dickson et al, 2009).…”
Section: Transcriptome Analyses Of Cell Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Inamori et al (2020), the repository source of the mice was missing in the Acknowledgment Section.…”
mentioning
confidence: 99%